2022
DOI: 10.1007/s00125-022-05672-y
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of beta cells: lessons from in vivo and in vitro models

Abstract: The ability to maintain normoglycaemia, through glucose-sensitive insulin release, is a key aspect of postnatal beta cell function. However, terminally differentiated beta cell identity does not necessarily imply functional maturity. Beta cell maturation is therefore a continuation of beta cell development, albeit a process that occurs postnatally in mammals. Although many important features have been identified in the study of beta cell maturation, as of yet no unified mechanistic model of beta cell functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 151 publications
(213 reference statements)
1
19
0
Order By: Relevance
“…Our study is unique in that we found that most of the metabolic and exocytosis pathways related to beta cell maturation [ 40 ] were upregulated in CD81 low beta cells, with some difference in DEPs (such as PDX1 [ 41 ]), through single-cell proteomics, findings which are not replicated in scRNA-seq. Since the protein is the executor of biological function, these could suggest that CD81 low beta cells are functionally mature.…”
Section: Discussionmentioning
confidence: 95%
“…Our study is unique in that we found that most of the metabolic and exocytosis pathways related to beta cell maturation [ 40 ] were upregulated in CD81 low beta cells, with some difference in DEPs (such as PDX1 [ 41 ]), through single-cell proteomics, findings which are not replicated in scRNA-seq. Since the protein is the executor of biological function, these could suggest that CD81 low beta cells are functionally mature.…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting to note that the expression of TGFB1 gene was also up-regulated in islets from 7-day-old compared to islets from 3-day-old pigs. TGFÎČ1 has been shown to play diverse roles in the development, proliferation, apoptosis, dedifferentiation, and function of islet beta cells in humans and rodents ( 37 – 39 ). For example, rat islets treated with TGFÎČ1 stimulates insulin secretion in low glucose condition but has no effect in high glucose condition ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ucn3 KO mice were recently generated and reported to have no deficit in beta cell maturation or function, deeming Ucn3 a marker, but not a driver of maturation (Huang et al, 2020). Many other maturation markers have been postulated through studies of mouse development, human diabetes, or by studying human SC-islets, but lack corresponding evaluation comparing mature adult vs. immature fetal human tissues (Zito et al, 2010;Veres et al, 2019;Barsby and Otonkoski, 2022). Arda et al provided an important resource with their 2016 publication assessing single-cell human beta cell transcriptomes, identifying several genes that significantly change expression during early postnatal development (Arda et al, 2016).…”
Section: Open Access Edited Bymentioning
confidence: 99%